Sleep related movement disorders in the elderly: a review of recent literature - Comair, Marc; Awad, Sandy; Ghosh, Pritha (Frontiers in Sleep, 2024)
Sleep-related movement disorders (SRMD) are common, often troublesome, conditions in the elderly. Although these disorders can impact people of all ages, there are different considerations when diagnosing and managing SRMD in the elderly. In this review, we discuss SRMD in the elderly, focusing on recent developments in the areas of restless leg syndrome, periodic limb movement disorder, nocturnal muscle cramps, and sleep-related bruxism. In addition to reviewing these entities more generally, we highlight key considerations in addressing these in conditions in older adults.